A Study on the Specific Growth Rate (SGR) at Different Stages of Tilapia (Oreochromis niloticus) Production Cycle in Tank Based Aquaculture System - Md. Hashibur Rahman; Mohammad Mahfujul Haque; Mohammad Ashraful Alam; Flura (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
The conventional assessment of the specific growth rate (SGR) avoiding intermediary data is highly criticized by scholars as to the data of the beginning and the end of the production cycle usually considered for the measurement. To evaluate the SGR, the study was conducted in six concrete tanks under an outdoor laboratory shed from 10th May to 29th July 2017. Tilapia (Oreochromis niloticus) fry was released at the rate of 8 fries per tank as per the recommended stocking density of 320 fishes/decimal in an intensive aquaculture system. To evaluate the experiment, sinking and floating feeds as treatment 1 (T1) and treatment 2 (T2) were used for feeding the fish, respectively. There were three replications for each treatment. During the experimental period, the feed was supplied at the rate of 20%, 15%, and 10% of the body weight in the 1st, 2nd, and 3rd months, respectively. The daily ration of fish was divided into two parts and delivered to fish in the morning and in the evening. Aeration facilities were installed for 24 hours using an air stone aerator. Digital balance was used for measuring the weight of fish in 3 days intervals to assume the trend of SGR while a customized scoop net was used to sample the fish minimizing the stress on the fish. The weight gains of fish were 126.08±5.65 and 132.23±1.29 for T1 and T2, respectively. The mean percent weight gain was found higher in T2 (1715.03±0.00) than in T1 (1639.43±0.00). Feed conversion ratio (FCR) in T1 and T2 were 1.97±0.11 and 2.13±0.18, respectively. The specific growth rates (SGR) of tilapia in T1 and T2 were 4.90±3.03 and 4.98±2.28 considering the data at the beginning and the end of the production cycle, respectively. However, the SGR for floating feed was higher at the initial stage of the production cycle and lower in the later stages. The SGR was almost static for sinking feed from the beginning to the end of the experimental period. The higher FCR in T2 was correlated with the lower SGR in the later stage of the culture period. This ascertains that the pre-determined required amount of feeding ration imparted by the farmers in case of floating feed which wastes the high-cost feed and money. Higher total production was obtained in T2 (1119.52 g) than in T1 (1070.19 g) with 100% survival in both treatments. Therefore, determining SGR in a specific interval might be a useful tool at the farmer's level.